Keadilan Distribusi dalam Ekonomi Islam sebagai Solusi untuk Ketimpangan Sosial di Indonesia - Kurnia Fitri; Valina Sinka; Reni Ria Armayani Hasibuan (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
Social and economic inequality in Indonesia is a multidimensional challenge that is not only reflected in the gap in income and wealth, but also in unequal access to education, health, and economic opportunities. The conventional economic system is considered ineffective in overcoming the problem of fair distribution of wealth, thus widening the gap between the rich and the poor. This article aims to analyze the concept of distributive justice in Islamic economics as a solution to social inequality in Indonesia, by highlighting the synergy of zakat, waqf, sharia financing instruments, and the role of government and society. The method used is a systematic literature review with a qualitative-narrative approach to various related academic works. The results of the study show that the application of the principle of distributive justice in Islamic economics through the optimization of zakat, waqf, and alms, as well as strengthening sharia economic regulations and literacy, can reduce social inequality and improve community welfare. The implementation of an inclusive and sustainable Islamic distribution model can reduce the Gini coefficient and strengthen social solidarity, although it still faces challenges in terms of regulation, literacy, and institutional coordination. The conclusion of the study confirms that Islamic economics offers concrete and holistic solutions to overcome social inequality in Indonesia through the integration of divine values, community participation, and state policies that support distributive justice.